Kivy : interactive applications and games in Python : create responsive cross-platform UI/UX applications and games in Python using the open source Kivy library. /: interactive applications and games in Python : create responsive cross-platform UI/UX applications and games in Python using the open source Kivy library. (2015) - Ulloa, Roberto
No abstract available